EFEKTIVITAS KOMBINASI KOAGULAN SINTETIK DAN BIOKOAGULAN TERHADAP PENINGKATAN MUTU BAKU AIR SUNGAI TABALONG - Sari, Yunita; Fauzana, Noor Arida; Fitriliani, Indira; Herliwati, Herliwati (EnviroScienteae, 2023)
Tabalong River is used as the raw water source for PDAM Tabalong. The large number of industrial activities in the district produces residual products that eventually pollute the watershed, resulting in a decrease in water quality and availability. Parameters that do not meet the standard quality standards as clean water based on Government Regulation No. 22 of 2021 class I are turbidity, color, TSS, dissolved Fe, dissolved Mn, and E. coli. This river water requires treatment with coagulation - flocculation technology with the jar test method. The technology requires a coagulant whose role is to precipitate colloidal particles. The commonly used coagulant is poly aluminum chloride (PAC). It is abundant but produces high concentrations of sludge, so coagulants that are biodegradable, biocompatible, non-toxic, and abundant are needed. These properties are found in biocoagulants in the form of chitosan. The coagulant in this study is synthetic (PAC) and bicoagulant (chitosan) by determining the optimum dose in river water treatment in the rainy season. The optimum dose is used to combine the ratio between coagulants. The ratio is (100:0, 25:75, 50:50, 75:25, and 0:100) which is analyzed for its effectiveness from each parameter. The optimum dose of PAC is 10 ppm and chitosan is 20 ppm. The best effectiveness is the PAC-chitosan combination in the form of a ratio of 0:100, which is in the form of chitosan which is able to reduce the levels of these parameters to meet the quality standards.